Efficiency Analysis of Turkish Banking Sector by Provinces (Third Sector Social Economic Review, 2026)
The banking sector, as one of the primary drivers of economic development, plays a decisive role in the efficient allocation of resources. However, regional disparities often lead to varying levels of output in banking services. This study measures the efficiency of the Turkish banking sector at the provincial level using Data Envelopment Analysis (DEA). Furthermore, it aims to identify the factors contributing to regional efficiency differentials and their respective degrees of impact. To achieve this, Tobit regression and clustering analysis methods were employed. Factors affecting efficiency were identified both structurally and on a province-specific basis.Using the Turkish Banks Association database, provincial-level data including the number of personnel, total assets, and deposits were utilized as inputs, while sales and total loans were selected as output variables for the efficiency analysis. Additionally, given the diverse development and commercial activity levels across Turkish provinces, Tobit regression and clustering analyses were conducted to determine the predictors of efficiency scores and to control for structural differences among provinces.The empirical findings reveal significant performance disparities across provinces in the Turkish banking sector and identify the underlying factors driving these differences. The results indicate that provincial banking efficiency scores are largely independent of scale. Furthermore, the study demonstrates that efficiency levels vary based on a centralized management approach rather than local administrative practices at the provincial level. Factors influencing efficiency were found to differ primarily according to commercial variables. Another key finding suggests that the banking system is managed through a highly centralized framework, and the sector responds rapidly to market fluctuations at the provincial level.
Keywords: Efficiency analysis; Banking performance by provinces; Efficiency; data envelopment analysis; cluster analysis